EVALUASI KELAYAKAN TEKNIS JALAN LINGKAR SALATIGA - Kiki Trisnawati; Agnes Putri Wulandari; Bambang Riyanto; Moga Narayudha (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
Salatiga arterial ring road is one primary arterial road, that connect the capital city of central java’s Semarang and Surakarta capital city. Salatiga arterial ring road was estabilashed with the purpose that the continuous trafficing between Semarang-Surakarta could be alternated without passing city, so the traffic jam will be reduced. The construction of Salatiga arterial ring road has been started since 2005 and the limited time of this road is 2016, so it needs some road pavement, road complement facility such as traffic sign s traffic performance, road pavement, road complement facility such as traffic sign, road markers, road light lamp and road drainage channel. This evaluation be done that for Salatiga arterial ring road still be maximumly functioned when serves the traffic movements.